Fiber network composed of interconnected yolk-shell carbon nanospheres for high-performance lithium-sulfur batteries. (December 2018) - Lin, Lele; Pei, Fei; Peng, Jian; Fu, Ang; Cui, Jingqin; Fang, Xiaoliang; Zheng, Nanfeng
Abstract: Lithium-sulfur (Li-S) batteries are a promising candidate for next-generation energy storage devices. However, rapid performance decay at high-sulfur-loading condition is emerged as one of the main obstacles restricting the practical application of Li-S batteries. Here we develop a facile electrospinning method for synthesizing the interconnected yolk-shell carbon nanospheres assembled fiber network to construct self-supporting sulfur cathodes. Benefiting from high surface area, nitrogen atom doping, and synergetic effect between yolk and shell, the yolk-shell carbon fiber network is a promising sulfur hosting material for high-sulfur-loading Li-S batteries. With 70 wt% and 4 mg cm −2 of sulfur, the yolk-shell carbon fiber network derived self-supporting cathode exhibits a high capacity retention of 82.8% after 500 cycles at 1 C. In addition, the self-supporting cathode with 16 mg cm −2 of sulfur delivers a stable areal capacity of 15.5 mAh cm −2 . This work provides a new strategy for the development of high-performance Li-S batteries. Graphical abstract: Fiber network composed of interconnected yolk-shell carbon nanospheres is synthesized via a facile templated electrospinning method. With the favorable structural parameters, this fiber network is a promising sulfur hosting material for constructing the high-sulfur-loading Li-S batteries with enhanced performance. Highlights: Yolk-shell structured carbon fiber network is designed and synthesized as a sulfur hosting material. Yolk-shell structure has a synergetic effect on the suppression of polysulfide shuttling. The as-prepared fiber network endows high-sulfur-loading Li-S batteries with significantly improved electrochemical performance.